Impact of Clostridioides difficile infection on the outcome of patients receiving a hematopoietic stem cell transplantation. (October 2020) - Weber, Sarah; Scheich, Sebastian; Magh, Aaron; Wolf, Sebastian; Enßle, Julius C.; Brunnberg, Uta; Reinheimer, Claudia; Wichelhaus, Thomas A.; Kempf, Volkhard A.J.; Kessel, Johanna; Vehreschild, Maria J.G.T.; Serve, Hubert; et al.
Highlights: C. difficile infections (CDI) do not impact survival of stem cell recipients. CDI are more frequent in allogeneic vs. autologous stem cell patients. Main cause of death is relapse in non-CDI patients, but infections in CDI patients. Abstract: Objectives: Clostridioides difficile infections (CDI) are common in autologous (auto-HSCT) or allogenic hematopoietic stem cell transplant (allo-HSCT) recipients. However, the impact of CDI on patient outcomes is controversial. We conducted this study to examine the impact of CDI on patient outcomes. Methods: We performed a retrospective single-center study, including 191 lymphoma patients receiving an auto-HSCT and 276 acute myeloid leukemia (AML) patients receiving an allo-HSCT. The primary endpoint was overall survival (OS). Secondary endpoints were causes of death and, for the allo-HSCT cohort, GvHD- and relapse-free survival (GRFS). Results: The prevalence of CDI was 17.6% in the AML allo-HSCT and 7.3% in the lymphoma auto-HSCT cohort. A higher prevalence of bloodstream infections, but no differences concerning OS or cause of death were found for patients with CDI in the auto-HSCT cohort. [AU] In the allo-HSCT cohort, OS and GRFS were similar between CDI and non-CDI patients. However, the leading cause of death was relapse among non-CDI patients, but it was infectious diseases in the CDI group with fewer deaths due to relapse. Conclusions: CDI was not associated with worse survival in patients receiving a hematopoietic stem cell transplantation, and there were even fewer relapse-related deaths in the AML allo-HSCT cohort.